1990
DOI: 10.1002/cbf.290080202
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nuclear antigen with molecular weight of 48 000 differentially expressed in tumour and normal cells

Abstract: A non-histone protein with mol. wt of 48,000 differentially expressed in normal and tumour cells was identified using immunological criteria. Antibodies were raised against a component specific for Kirkman-Robbins hepatoma of mol. wt about 48,000 separated from hepatoma non-histone proteins by preparative electrophoresis in polyacrylamide gel. It was demonstrated by immunoblotting that Morris hepatoma 7777 and Ehrlich ascites cells share an antigenic non-histone protein with Kirman-Robbins hepatoma. Tumour cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…However most of the changes in NHPs were quantatively detected by biochemical methods such as column chromatography and SDSpolyacrylamide gel eletrophoresis. Unique proteins characteristic for neoplastic process have recently been observed using immunochemical detection [25,29,31,[33][34][35]521.The results of this study revealed that hepatoma-associated nonhistone protein antigens in rat hepatoma cells described recently by this laboratory [36] are also present in other rodent hepatoma, i.e., hamster Kirkman-Robbins hepatoma. Both hepatomas are transplantable and comprise poorly differentiated and very malignant tumor cells.…”
supporting
confidence: 46%
“…However most of the changes in NHPs were quantatively detected by biochemical methods such as column chromatography and SDSpolyacrylamide gel eletrophoresis. Unique proteins characteristic for neoplastic process have recently been observed using immunochemical detection [25,29,31,[33][34][35]521.The results of this study revealed that hepatoma-associated nonhistone protein antigens in rat hepatoma cells described recently by this laboratory [36] are also present in other rodent hepatoma, i.e., hamster Kirkman-Robbins hepatoma. Both hepatomas are transplantable and comprise poorly differentiated and very malignant tumor cells.…”
supporting
confidence: 46%